An organic–inorganic hybrid photocatalyst based on sandwich-type tetra-Co-substituted phosphotungstates with high visible light photocatalytic activity1. Issue 31 (21st August 2015) - Song, Bai-Qiao; Wang, Xin-Long; Sun, Chun-Yi; Zhang, Yu-Teng; Wu, Xue-Song; Yang, Liu; Shao, Kui-Zhan; Zhao, Liang; Su, Zhong-Min
<x xml:space="preserve">Abstract</x> A novel hybrid photocatalyst constructed from tetra-CoII-substituted sandwich-type phosphotungstates exhibits highly efficient visible light photocatalysis activity.